2020
DOI: 10.3892/ijo.2020.5048
|View full text |Cite
|
Sign up to set email alerts
|

Upregulated expression of SAC3D1 is associated with progression in gastric cancer

Abstract: SAC3 domain containing 1 (SAC3D1) has been reported to be involved in numerous types of cancer. However, the role of SAC3D1 in GC has not yet been elucidated. In the present study, the mRNA expression level of SAC3D1 between GC and normal tissues were assessed with a continuous variable meta-analysis based on multiple datasets from public databases. The protein expression level of SAC3D1 in GC and normal tissues was assessed by an in-house immunohistochemistry (IHC). The association between SAC3D1 expression a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…As a malignancy of the digestive system, gastric cancer (GC) originates in the gastric mucosal epithelium (1). Based on global cancer statistics in 2020, more than one million patients were newly diagnosed with GC and ~769,000 patients died from GC; GC ranks fifth in incidence and fourth in cancer-associated mortality of all types of cancer (2).…”
Section: Introductionmentioning
confidence: 99%
“…As a malignancy of the digestive system, gastric cancer (GC) originates in the gastric mucosal epithelium (1). Based on global cancer statistics in 2020, more than one million patients were newly diagnosed with GC and ~769,000 patients died from GC; GC ranks fifth in incidence and fourth in cancer-associated mortality of all types of cancer (2).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that RGS20 promotes the development of cancer by regulating the PI3K/AKT signal pathway in cancer cells [39] . The expression level of SAC3D1 [ 40 , 41 ], PPP2CA [ 42 , 43 ], PTTG1IP [44] genes is significantly increased in tumor cells and can be used as a cancer marker.…”
Section: Discussionmentioning
confidence: 99%
“…Sensitivity analysis was used to explore potential sources of heterogeneity, and publication bias test was applied to assess the stability of SMD results. Simultaneously, the summary receiver operating characteristic (SROC) curve, the diagnostic specificity and sensitivity, and the Fagan graph were created to evaluate the ability of ARNT2 expression levels to identify cancer and noncancer samples [15][16][17].…”
Section: Detecting Arnt2 Mrna Expression Level Throughmentioning
confidence: 99%